2002
DOI: 10.1507/endocrj.49.531
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hyperglycemia Is a Strong Correlate of Postoperative Infection in Type II Diabetic Patients after Coronary Artery Bypass Grafting.

Abstract: This study was planned to assess the relationship of perioperative glycemic control to the subsequent risk of infectious complications and to compare early clinical outcomes of coronary artery bypass surgery in diabetics with nondiabetics in a single center. A total of 1090 adults who underwent coronary artery surgery in a five year period were included in a retrospective cohort study based on available chart review. Of 1090 patients, 400 had type II diabetes mellitus. Intraoperative and postoperative blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
104
3
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(117 citation statements)
references
References 20 publications
2
104
3
8
Order By: Relevance
“…In addition, postoperative hyperglycemia has been shown to be associated with an increased risk of surgical site infection (SSI) [11,12] . Current evidence suggests that maintaining normoglycemia postoperatively improves surgical outcome and reduces mortality and morbidity in critically ill patients [8,11,12] . These observations led to several short-lived multicenter randomized controlled studies designed to evaluate the benefit of tight glycemic control with intensive insulin therapy [13,14] .…”
Section: Current State Of Tight Glycemic Control In Critically Ill Pamentioning
confidence: 99%
“…In addition, postoperative hyperglycemia has been shown to be associated with an increased risk of surgical site infection (SSI) [11,12] . Current evidence suggests that maintaining normoglycemia postoperatively improves surgical outcome and reduces mortality and morbidity in critically ill patients [8,11,12] . These observations led to several short-lived multicenter randomized controlled studies designed to evaluate the benefit of tight glycemic control with intensive insulin therapy [13,14] .…”
Section: Current State Of Tight Glycemic Control In Critically Ill Pamentioning
confidence: 99%
“…Multivariate analysis showed age, obesity and diabetes mellitus (DM) as independent risk factors for this outcome [7]. In relation to DM, Guven et al [9] demonstrated that hyperglycemia at pre-CABG was the main risk factor for developing post-operative infections; risk can be reduced with improved glycemic control in the perioperative period [10]. Similar results were observed by some authors [11], but not by others [12].…”
Section: Introductionmentioning
confidence: 69%
“…O regime de controle glicêmico por meio ICI foi adotado em seis estudos primários (28,(32)(33)(34)(35)(36) . Uma pesquisa delimitou o controle glicêmico de 100-150mg/dL no perioperatório, usando o regime de ICI em pacientes com e sem diabetes, sendo que os resultados não apresentaram diferença estatisticamente significante na incidência de infecções pós-operatórias entre os grupos (28) .…”
Section: Discussionunclassified
“…de pacientes com diabetes foram identificados com infecção no PO e 2% no grupo de pacientes sem diabetes, os autores concluíram que o controle glicêmico no perioperatório é necessário para redução de complicações infecciosas no PO em pacientes com diabetes submetidos à CRM, sendo a hiperglicemia fator independente para complicações infecciosas e aumento no tempo de internação hospitalar (33) .…”
unclassified
See 1 more Smart Citation